Studies of microstructure and dielectric properties of CaCu3Mn4O12 complex perovskite oxide synthesized by chemical route - Kumar V.; Pandey S.; Singh S.; KumarVerma M.; Kumar A.; Singh N.B.; Mandal K.D. (My University, 2025)
CaCu3Mn4O12 (CCMO) ceramic was successfully synthesized by chemical route. The phase formation was to be examined by X-ray diffraction (XRD) pattern of the sintered pellet (850 °C for 6 h), and the crystalline size was found to be 21 nm. Raman shift observed at 3364 to 991 cm−1, clearly confirmed the existence of copper oxide phase at the grain and grain boundaries of the polycrystalline of CCMO complex perovskite oxide. The grain morphology of CCMO ceramic was studied by using HR-SEM, observing the needle-like phase. The particle size observed by TEM measurement was found to be 146.34 nm. The dielectric constant and dielectric loss were found to be 3.3 × 102 and 1.2 respectively. © 2020, Australian Ceramic Society.